Gonotrophic cycle estimate for Culex quinquefasciatus in Mérida, Yucatán, México - García Rejón, Julián Everardo; Fernández Salas, Ildefonso; Farfán Ale, José Arturo; Beaty, Barry J.; Ulloa García, Armando; Loroño Pino, María Alba; Flores, Luis; Rosado, Elsy (2008)
West Nile virus (WNV) has been present in the Yucatán State, México, since 2002. Culex quinquefasciatus, one of the main vectors of WNV transmission in the United States, is also common in Mexico and may be a key vector of WNV transmission to humans in the Yucatán. The aim of this study was to determine the length of the gonotrophic cycle and the survival rates of Cx. quinquefasciatus from Mérida, Yucatán, during the rainy versus the dry season. Mosquitoes were collected during 25-day periods in October (rainy season) and in April (dry season), and captured females were classified by abdominal appearance (freshly fed, late-stage fed, half gravid, and subgravid). To determine the age structure as nulliparous and parous females and to calculate the gonotrophic cycle through a time series and the mosquito survival, we used Davidson formulae. Also, vitellogenesis analysis to monitor egg maturity was conducted during both seasons. Cross-correlation data suggested a similar length of the gonotrophic cycle (4 days) in both seasons. Oogenic development required a minimum of 72 h in each season. However, survival of the mosquito population collected in the rainy season was significantly higher (0.91) with a mean temperature of 28 ± 1.57°C than was survival in the dry season (0.78) with a mean temperature of 29 ± 1.10°C. Survival, although higher during the rainy season, did not influence the length of the gonotrophic cycle of Cx. quinquefasciatus in Yucatán.